Question and answer
Suppose that the elimination method results in the equation 0=0. What does this indicate about the number of solutions to the system of equations?
If you have two different equations with the same two unknowns in each, you can solve for both unknowns. There are three common methods for solving: addition/subtraction, substitution, and graphing. [ Addition/subtraction method This method is also known as the elimination method. To use the addition/subtraction method, do the following: Multiply one or both equations by some number(s) to make
the number in front of one of the letters (unknowns) the same or exactly the opposite in each equation. Add or subtract the two equations to eliminate one letter. Solve for the remaining unknown. Solve for the other unknown by inserting the value of the unknown found in one of the original equations. Example 1 Solve for x and y. Adding the equations eliminates the y-terms. ] ]
Expert answered|aiambot17|Points 49|
Question
Asked 7/29/2012 10:13:28 AM
0 Answers/Comments
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
An investor invested a total of $2,400 in two mutual funds. One fund earned a 7% profit while the other earned a 5% profit. If the investor's total profit was $140, how much was invested in each mutual fund?
Weegy: $1,000 was invested at 7% (1000*.07=70) and $1,400 was invested at 5% (1400*.05=70). (More)
Question
Expert Answered
Asked 7/29/2012 9:59:11 AM
0 Answers/Comments
solve by the elimination method: 9a+3b=18 -9a+b=18
Weegy: 9a+3b = 18 -9a+b = 18 - - - - - - - 4b = 36 b = 9 Substituting b = 9 in -9a+b=18 -9a + 9 = 18 -9a=9 a = -1 (More)
Question
Expert Answered
Asked 7/29/2012 10:19:31 AM
0 Answers/Comments
3u+2v=-15 2u+v=-6
Weegy: U = 1, V = -10. (More)
Question
Expert Answered
Asked 7/29/2012 10:40:55 AM
0 Answers/Comments
3u+2v=-17 2u+v=-7
Weegy: U = 1, V = -10. User: 3u+2v=-15 Weegy: U = 1, V = -10. (More)
Question
Expert Answered
Asked 7/29/2012 10:28:56 AM
0 Answers/Comments
18,451,769 questions answered
Popular Conversations
Simplify 12A + 2 + A - 1. 14A - 1 13A - 1 13A + 1 User: ...
Weegy: 12(A - B) = 12A - 12B User: Simplify 10x - 3x + (-5x). -2x 2x 18x -18x Weegy: c.18x User: Simplify ...
11/25/2014 3:05:18 PM| 6 Answers
True or false carbohydrates are made up of carton, hydrogen, and ...
Weegy: The answer is True. Here is the source link: User: The two main types of fiber are?
11/25/2014 7:45:43 PM| 5 Answers
x + y = k x - y = k
Weegy: 8 1/3 - 1 5/6 = 25/3 - 11/6; = 50/6 - 11/6; = 39/6; = 13/2; = 6 1/2 User: 5x + y = 6 5x + 3y = -4 Weegy: ...
11/25/2014 9:09:05 AM| 4 Answers
Determine the solution set of (2x - 5)2 = 11.
Weegy: 2x - 3 = 9 2x = 9 + 3 2x = 12 x = 12/2 x = 6 User: Determine the solution set of (3x + 1)2 - 100 = ...
11/25/2014 11:37:07 AM| 4 Answers
The first English child born in the new world
Weegy: TRUE The first English child born in the new world
11/25/2014 1:29:56 PM| 4 Answers
20,000 pounds equals how many English tons?
11/25/2014 3:30:36 AM| 3 Answers
Simplify 20 + (2 + r). r + 22 22r 20r
Weegy: r + 22 User: Simplify (5a)(5b). 10ab 25ab 55ab Weegy: (5a)(5b) = 25ab User: Simplify 7.95 - 3.86 + ...
11/25/2014 8:53:09 AM| 3 Answers
Which personal pronoun best completes the sentence? How is it used? ...
Weegy: My father made my sister and ME blueberry pancakes for breakfast. The correct pronoun is: me; indirect object. ...
11/25/2014 9:42:28 AM| 3 Answers
t Object]User: y + 3 = 2x y + 4 = 3x If you use the comparison ...
Weegy: 31/8 and 25/8 User: What is the result of adding the system of equations? 2x + y = 4 3x - y = 6 x = 2 x = ...
11/25/2014 10:32:36 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: The correct factored form of the given equation x^2 + 3x - 4 = 0 is (x - 1)(x + 4) = 0. User: olve n3 + 2n2 ...
11/25/2014 11:30:00 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: (x - 3)^2 = 0 written in general form is: x^2 - 6x + 9 = 0 Expand (x - 3)^2 = x^2 - 3x - 3x + 9 = x^2 - 6x + ...
11/25/2014 11:33:47 AM| 3 Answers
Weegy Stuff
S
L
1
L
P
C
1
P
C
1
L
P
C
1
Points 2660 [Total 14370]| Ratings 10| Comments 2560| Invitations 0|Offline
S
L
Points 1455 [Total 3741]| Ratings 0| Comments 1455| Invitations 0|Offline
S
L
Points 777 [Total 1298]| Ratings 6| Comments 717| Invitations 0|Offline
S
1
L
1
L
P
P
L
P
Points 764 [Total 14138]| Ratings 0| Comments 764| Invitations 0|Offline
S
Points 735 [Total 767]| Ratings 1| Comments 725| Invitations 0|Offline
S
1
L
L
Points 273 [Total 6667]| Ratings 0| Comments 273| Invitations 0|Offline
S
L
Points 161 [Total 1457]| Ratings 3| Comments 131| Invitations 0|Offline
S
Points 86 [Total 86]| Ratings 1| Comments 76| Invitations 0|Offline
S
Points 50 [Total 50]| Ratings 0| Comments 0| Invitations 5|Offline
S
Points 46 [Total 46]| Ratings 3| Comments 6| Invitations 1|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.